2003
DOI: 10.1242/jeb.00603
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous gas exchange and the significance of respiratory water loss in scarabaeine beetles

Abstract: SUMMARYRespiratory water loss in insects is a controversial topic. Whilst earlier studies considered respiratory transpiration a significant component of overall water loss, to the extent that it was thought to be responsible not only for the evolution of discontinuous gas exchange cycles (DGCs) but also for variation in DGC patterns, later work repeatedly questioned its importance. In particular, investigations of the proportional contribution of respiratory transpiration to total water loss in species showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 83 publications
7
52
1
Order By: Relevance
“…A meta-analysis of DGC characteristics, habitat aridity and temperature provided support for the hygric hypothesis (White et al, 2007). Comparative studies also showed that xeric species modulate DGC characteristics to restrict RWL (Duncan and Byrne, 2000;Chown and Davis, 2003). To the best of our knowledge, work by Chown and Davis (2003) provides the only comparative study examining RWL associated with DGC, demonstrating that xeric species have reduced RWL rates correlated with DGC characteristics, e.g.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…A meta-analysis of DGC characteristics, habitat aridity and temperature provided support for the hygric hypothesis (White et al, 2007). Comparative studies also showed that xeric species modulate DGC characteristics to restrict RWL (Duncan and Byrne, 2000;Chown and Davis, 2003). To the best of our knowledge, work by Chown and Davis (2003) provides the only comparative study examining RWL associated with DGC, demonstrating that xeric species have reduced RWL rates correlated with DGC characteristics, e.g.…”
Section: Introductionmentioning
confidence: 88%
“…Comparative studies also showed that xeric species modulate DGC characteristics to restrict RWL (Duncan and Byrne, 2000;Chown and Davis, 2003). To the best of our knowledge, work by Chown and Davis (2003) provides the only comparative study examining RWL associated with DGC, demonstrating that xeric species have reduced RWL rates correlated with DGC characteristics, e.g. longer interburst phase, shorter burst phase and/or shorter cycle length.…”
Section: Introductionmentioning
confidence: 95%
“…Thus, more comparative studies focusing on the importance of RWL (e.g. Chown and Davis, 2003) should be encouraged in order to appreciate the real importance and processes of selection to reduce the spiracular component of WLR in insects, especially in small ectotherms, such as insects, whose metabolic rate and WLR are more susceptible to increasing temperature and declining rainfall, as predicted in many regions because of global warming (Chown, 2011;Chown et al, 2011).…”
Section: Research Articlementioning
confidence: 99%
“…The contribution of respiratory water loss (RWL) to dehydration has been analysed mostly in insects showing discontinuous gas exchange (DGE) (e.g. Chown and Davis, 2003;Lighton, 1992;Quinlan and Lighton, 1999). There are two RESEARCH ARTICLE 1 Departamento de Biodiversidad y Biología Experimental, Facultad de Ciencias Exactas y Naturales, Universidad de Buenos Aires, Ciudad Universitaria, C1428EHA, Buenos Aires, Argentina.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation